Digital Transformation and Financial Literacy as Drivers of Innovation and Financial Agility: Evidence from Family-Owned Businesses in Southeast Asia - Fahdiansyah, Restu; Aisyah, Siti (STI Policy and Management Journal, 2025)
This study investigates how digital transformation (DT) and financial literacy (FL) influence innovation capability (IC) and financial management effectiveness (FME) in family-owned small and medium enterprises (SMEs) across five Southeast Asian countries. Grounded in the resource-based view, the model positioned organizational learning (OL) and strategic agility (SA) as mediators linking DT and FL to performance outcomes. Data were collected through a cross-sectional survey of 300 respondents and analyzed using structural equation modeling (SEM). The findings reveal that DT primarily enhances OL, while FL exerts a stronger influence on SA. Both OL and SA significantly drive IC, which in turn positively affects FME and firms’ competitiveness (FC). Additionally, FL is revealed to be a meaningful predictor of DT, suggesting that financially literate leaders are more likely to adopt and implement digital tools effectively. This study also uncovers cross-country differences in path strengths, reflecting how institutional context shapes capability development. While all core hypotheses are supported, this study is limited by its cross-sectional design, reliance on selfdeveloped measurement items, and partial regional scope. This study contributes to the literature on SMEs’ internal capacity-building by highlighting the complementary roles of digital and financial competencies in enhancing innovation and strategic outcomes within family-owned business context.